An expanded holistic model of healthy workplace practices. Issue 5 (18th July 2019) - O'Donnell, Mark; Ruth-Sahd, Lisa A.; Mayfield, Clifton O.
Abstract : Purpose: The purpose of this paper is to test whether supportive workspace design, cultivation of high-quality leader–member relationships and vision alignment explain incremental variance in job satisfaction, work engagement and overall life satisfaction beyond antecedents identified in an earlier model of healthy workplace practices. Design/methodology/approach: This paper reports the results of a survey study with a diverse sample of 214 employees. Findings: In a series of regression analyses, the findings revealed that supportive workspace design, cultivation of high-quality leader–member relationships and vision alignment each explain incremental variance in one or more outcome variables (job satisfaction, work engagement and overall life satisfaction) beyond that of antecedents identified in an earlier model of healthy workplace practices. Research limitations/implications: The present study identifies additional important variables to consider when conducting future research on healthy workplace practices. Future research could use longitudinal or experimental designs to further investigate the causal direction of the relationships identified in the present paper. Practical implications: Managers can implement the practices identified in this paper to improve employees' work engagement, job satisfaction and overall life satisfaction. Social implications: This paper offers insights about how to improve employees' lives, and thus, the potential impact is far-reaching and meaningful. Originality/value: This paper empirically assesses workplace variables that were not included in tests of the prior healthy workplace practices model.